Establishment of a clinical workflow for in vivo Raman spectroscopy during head and neck cancer surgery - Ayman Bali; Thomas Bitter; Mussab Kouka; Jonas Ballmaier; Ines Latka; Florian Windirsch; David Pertzborn; Nadja Ziller; Marcela Mafra; Nikolaus Gaßler; Jürgen Popp; Anna Mühlig; et al. (Scientific Reports)
Abstract As first part of an ongoing prospective feasibility trial (DRKS00028114) this work explored the integration of in vivo Raman spectroscopy (RS) into the routine setting workflow of head and neck cancer (HNC) surgery. In vivo RS was performed intraoperatively on 30 patients with HNC cell carcinoma and 10 patients with inflammatory diseases as a control group. A standardized process was established using a Raman system complied with stringent medical device regulatory standards. Spectra were collected in vivo from the tumor site, the tumor margins, and healthy tissue. The learning curve of the HNC team significantly improved measurement times from over 30 min initially to 2 min after 15 patients. Data from 35 patients were interpretable, demonstrating clear spectral differences between tumor and healthy tissues. The intraoperative in vivo RS workflow is now well established and is being used in the ongoing clinical trial.